Oxygen and disorder effect in the magnetic properties of manganite films - Sirena, M. (2004)
Fil: Sirena, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina